Analisis Pengaruh Keterikatan Kerja, Iklim Organisasi dan Kepuasan Kerja Terhadap Kinerja Karyawan PT XYZ - Michelle Michelle; Rostiana Rostiana (Universitas Tarumanagara, 2020)
This study aims to explain the role of work engagement, organizational climate, and job satisfaction on employee performance at PT XYZ. This research is a causality research conducted by cross sectional method. The sampling technique is done by convenience sampling. Data collection was carried out using a questionnaire instrument which was then analyzed using multiple linear regression analysis. The results of the study explained that work engagement, job satisfaction, and organizational climate play a positive role on the performance of employees at PT XYZ. These results explain that more employees feel they have a good attachment to the company, have satisfaction with the work done, and feel a conducive organizational climate that can support employees at PT XYZ to show better performance.